Information and Communication Technology (ICT) and Employee Performance: Relationship - Gharti, Amit (Nepal Journal of Multidisciplinary Research, 2023)
This paper aimed to gain an insight about the relationship between Information and Communication Technology (ICT) and employee performance at Private Management Colleges in the Kathmandu District. Descriptive analysis was used to explore the dimensions of academic performance. To conduct this research, a quantitative methodology was employed. Questionnaires was the main instrument used for the data collection. The study restricts to the private management colleges and institutions only. A Total of 45 teaching faculties of Kathmandu district were selected for the study to explore the use of ICT in relation to the employee performance. Individual consent was taken for ethical consideration. Mean, Standard deviation and Correlation was adopted to measure the objectives. The findings showed that the role of ICT to uplift teaching and learning practice at Private Management College seems to be substantial in the current scenario. The performance of faculty members in private management colleges in the sense of efficiency of work (r=0.612**, p=0.00), planning the work(r=0.632**, p=0.00), creativity and innovation(r=0.547**, p=0.00) and making effort(r=0.454**, p=0.02) was significantly contributed by the use of ICT. ICT played a significant role to uplift the performance of faculty members of private management college of the Kathmandu district. All the results presented so far in the study have been found to be indicating strong and positive relationship between ICT and employee performance. Statistically, it can be concluded in one sentence that if one point changes in ICT, it can bring 4 to 6 times positive changes in employee performance. In the future, the researcher should also investigate the impact of workforce diversity on team performance.